KETAHANAN BAMBU PETUNG (Dendrocalamus asper Backer) YANG DIAWETKAN DENGAN CCB TERHADAP SERANGAN PENGGEREK DI LAUT - Mohammad Muslich; Sri Rulliaty (BRIN Publishing, 2014)
Bamboo is a lignocellulosic material that susceptible to insect attack including marine borers. This paper studies the CCB treated bamboo petung (Dendrocalamus asper Backer) against marine borers in open water environment. Fifteen of four meters long bamboo were selected and divided into three height positions: base, mid and top. From each position, fifteen specimens of 30 cm length and 5 cm width were prepared as untreated samples and another fifteen samples were treated with 3% CCB using modified Boucherie proses for seven days. Preservative retention and penetration were recorded prior to open sea water exposure for six months. The results shows that all samples were attacked by marine borers in various level. CCB treated samples were classified as mild attack, while untreated samples were heavily attacked by marine borers. Anatomical properties of petung bamboo has a network of vascular bundles consisting of phloem metaxilem and large diameter, severely preserved. The average of CCB retention of samples taken from the base is 13.62 kg/m³, while the middle and top obtained retention of 11.47 kg/m³ and 9.12 kg/m³ respectively. Modified Boucherie process achieved 100% penetration to all samples observed. Marine borers identified namely Teredo sp. and Martesia striata.